Transformation of the Paradigm of Arabic Language Learning Based on Student-Centered Learning: A Systematic Literature Review Study (2015–2025) - Elva Nurhidayah; Hakmi Wahyudi (Universitas Islam Negeri Palopo, 2026)
This study examines the implementation of Student-Centered Learning (SCL) in Arabic language learning by analyzing its forms, effectiveness, and implementation challenges. Using a Systematic Literature Review (SLR) based on PRISMA guidelines, articles were retrieved from Google Scholar using the keywords “Student-Centered Learning” AND “Arabic Learning” for the period 2015–2025. From 1,470 identified studies, 16 articles met the inclusion criteria and were analyzed through thematic synthesis focusing on SCL models, learning outcomes, and implementation factors. The findings reveal that Project-Based Learning (PjBL), Task-Based Language Teaching (TBLT), and collaborative blended learning are the most frequently applied SCL models and are effective in improving students’ productive skills, motivation, confidence, and engagement. Nevertheless, challenges persist, including limited teacher competence, a lack of authentic learning resources, insufficient institutional support, and infrastructural constraints. This study is among the first SLRs to specifically examine SCL implementation in Arabic language learning within the Indonesian context. The findings provide practical insights for teachers, curriculum designers, and policymakers to strengthen the design and implementation of SCL-oriented Arabic language instruction.